2018
DOI: 10.1101/465757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The landscape of viral associations in human cancers

Abstract: Potential viral pathogens were systematically investigated in the whole-genome and transcriptome sequencing of 2,656 donors as part of the Pan-Cancer Analysis of Whole Genomes using a consensus approach integrating three independent pathogen detection pipelines. Viruses were detected in 382 genomic and 68 transcriptome data sets. We extensively searched and characterized numerous features of virus-positive cancers integrating various PCAWG datasets. We show the high prevalence of known tumor associated viruses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
150
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(163 citation statements)
references
References 60 publications
(58 reference statements)
13
150
0
Order By: Relevance
“…Out of these, 27 taxa remained being likely cancer-associated after extensive filtering. While studies on the viral metagenome of caner tissues and patients have been performed using datasets from cancer genomics studies 4,5,21,22 , similar large studies looking at the bacterial metagenome are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of these, 27 taxa remained being likely cancer-associated after extensive filtering. While studies on the viral metagenome of caner tissues and patients have been performed using datasets from cancer genomics studies 4,5,21,22 , similar large studies looking at the bacterial metagenome are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the viral metagenome of cancer tissues mainly identified known associations of Human Papillomavirus with cervical and head and neck cancer, Hepatitis B in liver cancer and Human Herpesvirus 5 in a variety of cancers while detection of Human Mastadenovirus C was controversial 4,5,21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of virus species including retroviruses, flaviviruses and herpesviruses, might contribute to the development of human diseases including autoimmune diseases and cancers. For example, Epstein-Barr virus (EBV) has been reported to play a causative role for head-neck cancer and lymphoma (Zapatka et al, 2020), and possibly for multiple sclerosis and systemic lupus erythematosus (Harley et al, 2018). It remains to be determined, however, which viruses are present in normal tissues and whether their state of activation contributes to disease development.…”
Section: Introductionmentioning
confidence: 99%